The Effect of Sildenafil on Recuperation from Sciatic Nerve Injury in Rats - Mehmet Fatih Korkmaz; Mehmet Fethi Ceylan; Hakan Parlakpınar; Mustafa Sağır; Levent Ediz; Emine Şamdancı; Ersoy Kekilli (Balkan Medical Journal, 2016)
Background: Severe functional and anatomical defects can be detected after the peripheral nerve injury. Pharmacological approaches are preferred rather than surgical treatment in the treatment of nerve injuries.